SAT0388 Factors associated with the persistence of articular symptoms in patients with chikungunya fever – chikbrasil cohort. (12th June 2018) - Marques, C.; Duarte, A.; Dantas, A.; Ranzolin, A.; Cavalcanti, N.; Medeiros, M.; Bezerra, M.; Marques, V.; Rocha, L.; Melo, P.; Valadares, L.; da Fonte, C.; et al.
Abstract : Background: Chikungunya Fever (CHIK) may evolve chronically with joint impairment, often disabling, which leads to a functional and quality of life impact. The CHIK outbreak in Brazil began in 2015, reaching its peak in 2016, particularly in the Northeast of the country, with 2 35 136 reported cases. Since this is the first epidemic of CHIK in Brazil, data on persistent post-acute joint disease are scarce, and this knowledge is of fundamental importance in defining the long-term impact of the disease. Objectives: To evaluate factors associated with persistence of the joint symptoms in CHIK patients. Methods: The CHIKBRASIL cohort is a prospective, multicenter, observational study, conducted in six research rheumatology centres from the Northeast of Brazil, and has enrolled CHIK patients with joint manifestations since April 2016. 1 Data from 207 patients followed up to December 2017 were analysed. Results: The mean age was 54.7 years, most female (90.3%); 39.1% of the patients had a diagnosis of previous rheumatic disease (49.4% osteoarthritis). The most frequent initial clinical manifestations were arthralgia (98.1%), fever (95.6%), morning stiffness (92.3%) and arthritis (88.9%). The first evaluation with the rheumatologist occurred at a median time of 12 weeks after the onset of symptoms; at this time the median PGA of disease by the patient was 7 and by the physician was 6; the median number of painful joints was 8 and of swollen joints was 3% and 75.5% of the patients had arthritis. After a median follow-up time of 37 weeks, there was complete improvement of joint symptoms in 21.7% and 18.9% of cases reported little or no improvement. The persistence of arthralgia was reported by 76.7% and arthritis by 28.1% of the patients. A significant association was found between the persistence of arthritis and the physician's general VAS (p=0.02), number of painful (p=0.002) and swollen (p=0.001) joints, besides knees (p=0, 009), proximal interphalangeal (p=0, 07), metacarpophalangeal (p=0, 022), elbow (p=0, 026) and wrist oedema (p=0, 003) at the first consultation). With regard to the persistence of joint pain, associations were found with a higher initial morning stiffness time (p=0.011), shoulder tendinopathy (p=0.019) and tarsal pain. The factors associated with no complete improvement after the follow-up period were tarsal pain (0, 021) and shoulder tendinopathy. Conclusions: In the Brazilian CHIK patients, the percentage of persistence of joint manifestations is high after 24 weeks, with a considerable number of patients maintaining arthritis, similar to other countries in Latin America. 2 Significant associated factors were more severe initial symptoms, polyarthritis, polyarthralgia, shoulder tendinopathy and tarsal pain. References: [1] Marques CDL, Cavalcanti N, Luna M, et al. Arthritis Rheumatol [Internet]201620-nov-2016;68(S10). [2] Chang AY, Encinales L, Porras A, et al. Arthritis Rheumatol 20172017Dec 20. doi:10.1002/art.40384 Disclosure of Interest: None declared